Research of Robots in Cooperative Mode in Human Body Part Detection - Ponikelsky, Josef; Cernohlavek, Vit; Sterba, Jan; Houska, Pavel (Manufacturing Technology Journal, 2023)
The aim of this article is to approach the measurement of forces and pressures of collaborative robots. In the article, research will be carried out on measuring the forces and pressures of a collaborative robot before putting it into real application. Force and pressure values will be measured using appropriate measuring devices. The measured results will be compared with the ISO/TS 15066:2016 technical specifi-cation and subsequently evaluated.
Keywords: Collaborative robot; measurement of forces and pressures; occupational safety; ISO/TS 15066:2016